UNVEILING THE CHEMICAL RICHES OF ORIGANUM ACUTIDENS: A QUEST FOR BIOACTIVE MOLECULES - Jones, Sarah; Hassan, Ahmed (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Origanum species, such as Origanum acutidens, are valued for their rich essential oil constituents and find diverse applications in culinary and folk medicine. This study investigates the isolation and structural identification of key bioactive compounds from O. acutidens, revealing the presence of rosmarinic acid, lithospermic acid, vicenin-2, betulalbuside A, 8OH-linaloyl glucoside, ursolic acid, and oleanolic acid metabolites. These compounds contribute to the plant's various biological properties, including antioxidant, antibacterial, and insecticidal activities. O. acutidens remains a promising source of phytochemicals with potential applications in the food and pharmaceutical industries.